Introducing a Model for Social Impact Assessment of Public Administration Reform in Romania - Raluca ANTONIE (Transylvanian Review of Administrative Sciences, 2012)
Social impact assessment (hereafter, SIA) is a specific type of evaluation extremely useful in public management, a research technique and a public policy instrument successfully used all over the world by those responsible with institutional and organizational management, with the coordination of projects and programs financed from public or private founds. Governments use the SIA in order to notice, in time, the effects of the interventions they implement or they intend to implement. The aim of a model for social impact assessment of public administration reform is to observe over time and mitigate the unwanted effects of public administration reforms on the groups of people, on communities and on society, as well as to encourage the positive elements of the impact. In short, social impact assessment of public administration reform can be used in order to minimize losses and maximize the benefits of the reform interventions upon small or large social groups.